The Teaching Learning Process of Vocabulary At English Department of Muhammadiyah University of Surakarta : A Micro Ethnography - Hastuti, Puji (2012)
This study is carried out to describe the teaching-learning process of vocabulary at English Department of Muhammadiyah University of Surakarta. The study is also intended to give some contribution for the betterment of teaching vocabulary. The data of this research are in the form of excerpts transcribed from the lecturer's attitude and interview in vocabulary class. The writer takes two vocabulary lecturers who teach the first semester students at English Department in 2011/2012 academic year of UMS as the subject of the research. The writer uses descriptive qualitative especially the ethnography research in analyzing the data. In conducting this study there are at least nine major stages that have been done: the learning objective, the materials, the syllabus, the methods which include procedures and techniques, the classroom activities, teacher roles, student roles, the evaluation system and the weaknesses and strengthens on teaching on teaching vocabulary. The result of the study shows that the application on the learning objective, the materials, the syllabus, and the methods followed the direction of Sabroni's book on teaching vocabulary and in addition the lecturers improve them in the class. In general, they run smoothly but there are limited variations in the method. The lecturers must give the innovation and be creative in teaching learning process on vocabulary class.